MOTIVASI KEPALA DESADALAM PEMBANGUNAN EKONOMI (Studi Kasus Pada Wilayah Desa Hargomulyo, Gedangsari, Gunung Kidul) - Widodo Widodo; Indri Astuti (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
The research aims to answer the formulation of the problem of what motivates and what the village head does in economic development?This research is a literature study of the Motivation of Village Heads in Economic Development in the Hargomulyo Village.The method used is to use descriptive qualitative research.The results of the study show that in economic development it can be carried out well because of coordination with superiors and subordinates and program regularly, facilitating education, reducing the cost of developing Early Childhood Education (ECED). Building traditional markets, increasing family planning (KB) programs, forming small business groups, making it easy for information businesses to enter the village, improving Intellectual Quation (IQ), Emotional Quation (EQ), Spiritual Quation and Creativity Quation (CQ), conducting counseling and Holding a Joint Farmers Group (GAPOKTAN) and increasing the selling price of agriculture also made tofu factories and tempe factories.Suggestions are aimed at improving education for citizens in general and Hargomulyo village officials in particular, Hargomulyo village officials and their citizens are always vigilant and prevent the arrival of miransantika and diligent worship according to the provisions of each religion, in the sense not to deviate from the religious teachings that have been adopted, because the deviation of religious teachings will hamper worship and the economy.